Competency Model of Iranian Public Administers - Ahmad Ali Khaef Elahi; Ali Rezaean; Roya Asadifard (Universiti Sains Islam Malaysia, 2024)
Now competent managers are one of the most important factors in organization successfulness whether in public sector or private. So have been increased researches in field of managerial competencies in recent decades. This research designed with aim of attainment to competency model of Iranian public administers. The first with investigate on literature with regard to carried out researches in competences in public and private sector emphasized on competency concept and then used grounded theory approach ,for capture a rigorous and scientific model. In the first stage of grounded theory is that open coding, 22 vol text of Sahifah (consist of lmam Khomeini speeches and writings) codified and in the axial coding stage after capturing main categories and subcategories presented competency model of Iranian public administers in based of Imam 'Sahifah . Validity and reliability test carried out by expertise in relevant fields also. At result competency model of Iranian public administers consist of seven main category which each category have subcategories. Theses main competencies are Sewing, Being Islamic, and being with people, non attention to self-interest, accountability, personal competencies. Finally in the selective coding stage, Serving generated as a core category of competency model and core competency of Iranian public administers.